Pro-environmental employee engagement: the influence of pro-environmental psychological capital, pro-environmental job resources, and perceived corporate environmental responsibility - Albrecht, Simon L.; Donnelly, Teagan; Frenkiel, Michael; Rajic, Stefan K.; Kavadas, Vicki; Leiter, Michael P. (Frontiers in Sustainability, 2023)
Introduction: For organizations to achieve their environmental obligations and objectives, they need employees to actively engage with environmental policies, practices, procedures, and initiatives. Based on engagement theory, a model is proposed that shows how perceived corporate environmental responsibility, pro-environmental job resources, and pro-environmental psychological capital influence employee pro-environmental engagement at work. Methods: Survey responses were collected from a Prolific sample of 347 full-time and part-time employees, aged 18-80, working within Australian organizations across a range of occupations. Results: Confirmatory factor analysis and structural equations modelling provided broad support for the measures and the relationships proposed in the model. The model explained 64% of the variance in pro-environmental job resources, 90% of the variance in pro-environmental psychological capital, and 92% of the variance in pro-environmental engagement. Discussion: Overall, the results suggest that for employees to feel enthusiastic and involved in pro-environmental initiatives at work, an integrated approach that takes account of perceived corporate environmental responsibility, pro-environmental job resources, and pro-environmental psychological capital is required. The results also provide brief, defensible measures of pro-environmental PsyCap, pro-environmental job resources and pro-environmental engagement that can be used to assess and target employee attitudes toward pro-environmental initiatives and opportunities. As such, the pro-environmental engagement model can help guide the design and implementation of evidence-based employee-focused interventions that will help achieve environmental sustainability objectives.